The Development of the Arms Industry in Poland in the Second Half of the 1930s. The Role of General Alexander Litwinowicz - Wojtaszak, Andrzej (Tools of War, 2023)
The face of the war threat, the economic effort related to the construction of the Central Industrial District and the implementation of the 6-year plan for the expansion and modernization of the Armed Forces was an action in the right direction, but overdue. The first stage of modernization and expansion of the Polish defense industry, increasing the defense capabilities of the Republic, was to be completed in 1942. This was accompanied by loans (French and British) and an increase in state spending on Polish defense. An important role in these endeavors was played by the Second Deputy Minister of Military Affairs, the head of the Army Administration, General Aleksander Litwinowicz, who, on behalf of the Armed Forces, supervised the implementation of plans related to the arms industry. The lack of sufficient budget funds for the purchase of weapons manufactured by Polish companies on the internal market forced the arms trade abroad, which was carried out (with the consent of the highest military authorities) almost until the outbreak of the war. 1939 not only showed Poland's military weakness, its loneliness in the face of failure to meet political and military alliances (France and Great Britain), but also the need for Poland to wage a war on two fronts. The German-Soviet alliance was a defeat not only for the Commonwealth, but also for post-universal Europe.